(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
This review article contributes to clarify physical and chemical properties of termite mound clay (Humbas meti) and potter wasp nest clay (Kumbal meti) which are traditionally used medicaments in Sri Lanka. Clay types enriched with cations are widely used as major mineral ingredients in traditional pharmaceutical science of Rasashastra (alchemy), Samhita grantha and Ayurveda pharmacopeia. Pharmaceutical products containing these two clay types have been used for different kind of diseases in different types of prescriptions; specially in Charaka Samhita for the disease named Urusthambha and also hydrocele (Mutraja vruddhi) and various edemas (Shotha). The main objective of this literature review was to discuss about physical and chemical properties of these two soil types and special objective was elucidate whether there is a linking between these chemical properties and curing ability. For the data collection of this study the detailed literature review was done on the chemistry and scientific basis of termite mound clay, Potter wasp nest clay and pharmaceutical applications was carried out using published Ayurveda text books and research articles, available from Science Direct. Research articles showed that termite mounds are frequently enriched with soluble salts such as ammonium nitrate, exchangeable basic cations such as Ca2+, Mg2+ and K+ and CaCO3 compared to the adjacent topsoil. Spectroscopic data revealed the presence of SiO2, and Al2O3 in appreciable quantities, while Fe2O3, CaO and MgO were in minor quantities in potter wasp nest clay. Infrared spectral analysis showed that nest clay samples are composite of quartz, feldspar and kaolinite. It is hard to find local research articles about physicochemical properties of these medicinally important clay types. 1Biotechnology Unit, Industrial Technology Institute, 363, Bauddhaloka Mawatha, Colombo 07, Sri Lanka. 2Institute of Indigenous Medicine, University of Colombo, Sri Lanka. *Correspondence: Research Scientist, Biotechnology Unit, Industrial Technology Institute, 363, Bauddhaloka Mawatha, Colombo 07, Sri Lanka. Email: beneetajayawardena@gmail.com